Supplementary data to 'The health and nutritional aspects of sustainable diet strategies and their relationship to environmental impacts – a comparative global modelling analysis with country-level detail' by Springmann et al - Springmann, M (University of Oxford, 2018)
The data contains the results of nutritional, health, and environmental analysis of dietary-change scenarios by region and country